متطلبات إعتماد الصكوك الإسلامية لتمويل البنى التحتية في الجزائر - جار الله عبد المنعم (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2025)
الملخص: تهدف هذه الد ا رسة إلى معالجة موضوع تمويل مشاريع البنى التحتية عن طريق الصكوك الإسلامية وهذا من خلال عرض أهم التجارب العالمية التي اعتمدت هذا النوع من التمويل، فتعدد مصادر التمويل وتنوعها واستقطابها من خارج مي ا زنيات الحكومة من أهم المسائل التي أثارت اهتمام الباحثين سواء أف ا ر دا، مؤسسات أو حتى حكومات، ومن مصادر التمويل التي لقيت اهتماما واسعا هي المنتجات المالية الإسلامية وأبرزها الصكوك الإسلامية وهذا لتنوعها ومرونتها وقدرتها على استقطاب الأموال من مختلف فئات المجتمع لتمويل مختلف المشاريع التنموية وبعوائد جيدة . ولتحقيق أهداف هذه الد ا رسة استخدمنا المنهج الوصفي والتحليلي المدعم بالبيانات والإحصائيات المتحصل عليها من مختلف الم ا رجع اولمؤسسات المالية، لاستنتاج مختلف آليات تمويل الصكوك الإسلامية لمشاريع البنى التحتية من خلال التجارب محل الد ا رسة . خلصت هذه الد ا رسة إلى أن الصكوك الإسلامية أداة مالية إسلامية ناجحة لتمويل مشاريع البنى التحتية والرفع من عجلة التنمية الاقتصادية وهذا عن طريق تعبئة الموارد المالية من مختلف فئات المجتمع وتمويل المشاريع التنموية، فبعد د ا رسة مختلف التجارب الدولية لاحظنا الفعالية الكبيرة للصكوك والإقبال المت ا زيد عليها سواء من طالبي التمويل والمستثمرين، وهذا رغم بعض الاختلالا ت الشرعية التي رصدت، كما قدمنا في هذه الد ا رسة أبرز الع ا رقيل والتحديات التي قد تعيق تطبيق الصكوك الإسلامية في الج ا زئر واقترحنا أهم الحلول التي تسهم في تجاوز ها وهذا عن طريق توفير البيئة القانونية، المالية والفنية لنجاح الصكوك الإسلامية والعمل على اعتمادها لتمويل مشاريع البنى التحتية في الج ا زئر . الكلمات المفتاحية: الصكوك الإسلامية – مشاريع البنى التحتية – المالية الإسلامية – التنمية الاقتصادية – قانون الصكوك – الأسواق المالية.Abstract : This study aims to address the issue of financing infrastructure projects through Islamic sukuk by presenting the most significant global experiences that have adopted this financing method. The diversification of funding sources, their attraction from outside government budgets, and their variety are among the key issues that have garnered the attention of researchers—whether individuals, institutions, or even governments. One of the funding sources that has received widespread interest is Islamic financial products, particularly Islamic sukuk, due to their diversity, flexibility, and ability to attract funds from various segments of society to finance development projects while offering favorable returns. To achieve the objectives of this study, we employed a descriptive and analytical approach supported by data and statistics obtained from various financial institutions and references. Additionally, we used the deductive method to derive different mechanisms for financing infrastructure projects through Islamic sukuk based on the studied experiences. The study concludes that Islamic sukuk is a successful Islamic financial instrument for financing infrastructure projects and accelerating economic development by mobilizing financial resources from various social groups to fund development initiatives. After analyzing multiple international experiences, we observed the high efficiency of sukuk and their growing demand from both financiers and investors, despite some recorded Shariah compliance issues. Furthermore, we identified the key obstacles and challenges that may hinder the implementation of Islamic sukuk in Algeria. The study also proposes essential solutions to overcome these challenges by establishing a supportive legal, financial, and technical environment for the successful adoption of Islamic sukuk in financing infrastructure projects in Algeria. Keywords : Islamic Sukuk – Infrastructure Projects – Islamic Finance - Economic Development – Sukuk Law – Financial Markets.
دراسة إستشرافية
Keywords: مشاريع البنى التحتية; التنمية الإقتصادية; المالية الإسلامية; البنى التحتية في الجزائر; المالية